Thoracic complications of central nervous catheterism - Croci, Fabio; Pérez Penco, Ernesto; Cordal, Adriana; Calleriza, Fernando (Cirugía del Uruguay, 1984)
Authors present thoracic complications of percutaneous central venous catheterisms, based on nine clinical observations of such complications. Authors discuss their etiopathiogenia, their treatment and their prophylaxis. Emphasis is laid on the necessity of accurate indication and impeccable technique.